Sepsis Progression to Multiple Organ Dysfunction in Carotid Chemo/Baro-Denervated Rats Treated with Lipopolysaccharide - Acuna-Castillo, C (Elsevier, 2015)
Sepsis progresses to multiple organ dysfunction (MOD) due to the uncontrolled release of inflammatory mediators. Carotid chemo/baro-receptors could play a protective role during sepsis. In anesthetized male rats, we measured cardiorespiratory variables and plasma TNF-α, glucocorticoids, epinephrine, and MOD marker levels 90. min after lipopolysaccharide (LPS) administration in control (SHAM surgery) and bilateral carotid chemo/baro-denervated (BCN) rats. BCN prior to LPS blunted the tachypneic response and enhanced tachycardia and hypotension. BCN-LPS rats also showed blunted plasma glucocorticoid responses, boosted epinephrine and TNF-α responses, and earlier MOD onset with a lower survival time compared with SHAM-LPS rats. Consequently, the complete absence of carotid chemo/baro-sensory function modified the neural, endocrine and inflammatory responses to sepsis. Thus, carotid chemo/baro-receptors play a protective role in sepsis. © 2014 Elsevier B.V.